ICT systems security and privacy protection : 35th IFIP TC 11 International Conference, SEC 2020, Maribor, Slovenia, September 21-23, 2020, Proceedings /: 35th IFIP TC 11 International Conference, SEC 2020, Maribor, Slovenia, September 21-23, 2020, Proceedings. (2020) - Unknown
No abstract available